Therapeutic Hypothermia in Transport Permits Earlier Treatment Regardless of Transfer Distance - Leon, Rachel L.; Krause, Katherine E.; Sides, Rebecca S.; Koch, Mary Beth; Trautman, Michael S.; Mietzsch, Ulrike (American Journal of Perinatology, 2020)
Objective Therapeutic hypothermia (TH) is currently the only effective therapy available to improve outcomes in neonates with hypoxic-ischemic encephalopathy (HIE) and has maximal effect when initiated within 6 hours of birth. Neonates affected by HIE are commonly born outside of cooling centers and transport is a barrier to timely initiation. In this study, we sought to determine if the initiation of servo-controlled TH in transport allowed neonates to reach target temperature earlier, without a significant delay in the transfer process, for both local and long-distance transport.Study Design In this single-center cohort study of neonates referred to a level IV neonatal intensive care unit for TH, we determined the chronologic age at which target temperature was reached for those cooled in transport. Short-term outcome measures were assessed, including survival, incidence of electrographic seizures, discharge feeding method, and length of hospitalization.Results In a study population of 85 neonates, those receiving TH during transport (n = 23), achieved target temperature (33–34°C) 77 minutes sooner (230 ± 71 vs. 307 ± 79 minutes of life (MOL); p < 0.001). Locally transported neonates (<15 miles) achieved target temperature 69 minutes earlier (215 ± 48 vs. 284 ± 74 MOL; p < 0.01). TH during long-distance transports allowed neonates to reach target temperature 81 minutes sooner (213 ± 85 vs. 294 ± 79 MOL; p < 0.01). Infants who were cooled in transport discharged 4 days earlier (13.7 ± 8 vs. 17.8 ± 13 days; p = 0.18) and showed a significantly higher rate of oral feeding at discharge (95 vs. 71%; p = 0.03).Conclusion For those starting TH in transport, time to target temperature was decreased. In our cohort, cooling in transport was associated with improved short-term outcomes, although additional studies are needed to correlate these findings with long-term outcomes.Key Points
Keywords: hypoxic-ischemic encephalopathy; neonatal transport; therapeutic hypothermia; birth asphyxia; active cooling; transport cooling; birth depression